2007
DOI: 10.1111/j.1365-2745.2007.01282.x
|View full text |Cite
|
Sign up to set email alerts
|

Reduced plant–soil feedback of plant species expanding their range as compared to natives

Abstract: Summary 1.As a result of global warming, species may spread into previously cool regions. Species that disperse faster than their natural enemies may become released from top-down control. We investigated whether plants originating from southern Europe and recently established in north-western Europe experience less soil pathogen effects than native species. 2. We selected three plant species originating from southern Europe that have immigrated into the Netherlands and three similar native Dutch species. All … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
129
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(136 citation statements)
references
References 68 publications
6
129
1
Order By: Relevance
“…Kulmatiski et al (2008) and Callaway et al (2011) suggested that missing plant-soil feedbacks may explain why some non-native plants become invasive and dominant in a new biogeographical range whereas others do not. The advantage of invasive species over native species in new ranges may, in addition, be due to negative soilfeedbacks affecting the native, but not the invasive plants (Klironomos 2002, van Grunsven et al 2007, although this effect may weaken over time in the new ranges as new enemies adjust to invasive species (Diez et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Kulmatiski et al (2008) and Callaway et al (2011) suggested that missing plant-soil feedbacks may explain why some non-native plants become invasive and dominant in a new biogeographical range whereas others do not. The advantage of invasive species over native species in new ranges may, in addition, be due to negative soilfeedbacks affecting the native, but not the invasive plants (Klironomos 2002, van Grunsven et al 2007, although this effect may weaken over time in the new ranges as new enemies adjust to invasive species (Diez et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Another approach focuses on whether plant-microbe interactions change as plants from warmer climates invade more northern habitats. Recent work, for example, suggested reduced soil pathogen effects (or, alternatively, increased soil mutualist activity) for plant species that moved into northwest Europe compared to plant species native to this region (133).…”
Section: Community and Ecosystem Ecologymentioning
confidence: 99%
“…Moreover, these range-expanders may experience less negative effects of soil organisms in their new range than congeneric natives (van Grunsven et al 2007;Engelkes et al 2008). This suggests that range shifts result in a release from natural enemies, which has been proposed as an important cause of invasiveness of introduced exotic species (Keane & Crawley 2002;Mitchell & Power 2003).…”
Section: Introductionmentioning
confidence: 93%
“…Nevertheless, within their new range, the few studies published thus far have shown that rangeexpanding plant species on average accumulate fewer pathogens and root-feeding nematodes, and are less negatively affected by soil communities than related native plant species (van Grunsven et al 2007;Engelkes et al 2008;Morriën, Duyts & Van der Putten 2012;Morriën & van der Putten 2013).…”
Section: State Of the Art: Plant-soil Interactions Of Intracontinentamentioning
confidence: 99%
See 1 more Smart Citation